Daidzein alleviates osteoporosis by promoting osteogenesis and angiogenesis coupling - Jia, Junjie; He, Ruiyi; Yao, Zilong; Su, Jianwen; Deng, Songyun; Chen, Kun; Yu, Bin (PeerJ, 2023)
Background Postmenopausal osteoporosis and osteoporosis-related fractures are world-wide serious public health problem. Recent studies demonstrated that inhibiting caveolin-1 leads to osteoclastogenesis suppression and protection against OVX-induced osteoporosis. This study aimed to explore the mechanism of caveolin-1 mediating bone loss and the potential therapeutic target. Methods Thirty C57BL/6 female mice were allocated randomly into three groups: sham or bilateral ovariectomy (OVX) surgeries were performed for mice and subsequently daidzein or vehicle was administrated to animals (control, OVX + vehicle and OVX + daidzein). After 8-week administration, femurs were harvested for Micro-CT scan, histological staining including H&E, immunohistochemistry, immunofluorescence, TRAP. Bone marrow endothelial cells (BMECs) were cultured and treated with inhibitors of caveolin-1 (daidzein) or EGFR (erlotinib) and then scratch wound healing and ki67 assays were performed. In addition, cells were harvested for western blot and PCR analysis. Results Micro-CT showed inhibiting caveolin-1with daidzein alleviated OVX-induced osteoporosis and osteogenesis suppression. Further investigations revealed H-type vessels in cancellous bone were decreased in OVX-induced mice, which can be alleviated by daidzein. It was subsequently proved that daidzein improved migration and proliferation of BMECs hence improved H-type vessels formation through inhibiting caveolin-1, which suppressed EGFR/AKT/PI3K signaling in BMECs. Conclusions This study demonstrated that daidzein alleviates OVX-induced osteoporosis by promoting H-type vessels formation in cancellous bone, which then promotes bone formation. Activating EGFR/AKT/PI3K signaling could be the critical reason.
Keywords: Osteoporosis; Angiogenesis; EGFR; Daidzein; Caveolin-1